ISAAA: Appropriate biotechnology - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
With the growing need for increased agricultural productivity in ACP States, many believe that biotechnology has a key role to play in improving the quantity and quality of crop yields. Provided they are properly integrated into production systems,...